Complex flow in tight oil reservoirs: A new perspective. (April 2023) - Du, Shuheng; Jin, Jun; Shi, Yongmin; Sun, Fuqiang
Abstract: This study aimed to investigate a new mechanism of complex flow in tight oil reservoirs impacted by heterogeneous minerals. In this study, a new classification scheme for seepage channels based on mineral types was firstly developed after considering the differences in their mechanical properties. There are nine types of seepage channels, consisting of four types of main minerals or mineral combinations. Results showed that the maximum flow velocity increases in a non–linear way as the average diameter of each type of seepage channel increases. Thus, the larger the diameter of the space, the greater the potential flow capability. As the injection pressure increases, the flow velocity could be higher in the larger seepage channels than the smaller seepage channels. When the oilfield enters the middle and later periods, in general, the oil in most of the large spaces has been removed. The average flow velocity (the comprehensive potential flow capability) has almost no relationship with the type of space; thus, a small space does not have a greater potential of exploitation than a large space. This conclusion points to a new direction for enhancing unconventional oil recovery. Highlights: Channels formed by various minerals dominate tight oil exploitation. The larger the diameter of the space, the greater the potential flow capability of oil. The comprehensive potential flow capability of fuel has no relationship with the space. A small space does not have a greater potential of exploitation than a large space.